Trilhando os caminhos do início da docência: concepções sobre o percurso formativo no processo de tornar-se professor - Lagoeiro, Aline de Cássia Damasceno (2019)
Teacher education is a continuous process that occurs throughout life and begins even before college, and teachers living experiences influence decision-making and pedagogical practices, contributing to their Professional constitution. The purpose of this research is to investigate the narratives of beginner teachers about the contributions of their formative path to the process of initiation to teaching. The research was based on the context of a collaborative online group called Rede de Aprendizagem e Desenvolvimento da Docência (ReAD) in the context of a “Project Teachers Induction Intergenerational Dialogue: the establishment of a continuous teacher education" funded by CNPQ and developed in the Moodle Platform, via UFSCar Portal of Teachers. It consisted of a formative activity, with an extension feature, offered to undergraduate students in Pedagogy, beginner and experienced teachers. The participants of the research are five teachers licensed in Pedagogy and who are at the beginning of their careers. The analyzed data refers to the activities developed in the Virtual Learning Environment (VLE) and to a narrative elaborated after the conclusion of the ReAD, contemplating aspects related to the formative path and pedagogical practices. In methodological terms, this research has a qualitative feature and was developed with the guiding parameters of the collective instrumental case study. About the production process and data analysis, the research is reasoned, respectively, in the use of narratives as an instrument of data production and prose analysis as a broader and more flexible analysis perspective, which we consider to be more appropriate to this study. The elements identified in the investigated reports contributed to broaden the understanding of teaching and professional teacher development. It was possible to notice the influence that the experiences and participants’ lives contexts exerted on various moments of their journey, from the choice of teaching to the necessary decision making at the beginning of their careers. The results highlight the role played by ReAD and the learnings provided through intergenerational online dialogue in the course of the developed activities. On the result of the analysis, it was verified that the stimulus to the resumption of their own experiences allowed participants a more articulate and reflective reading about their own trajectory. They could also recognize themselves in the experiences shared by the colleagues with whom they spoke and develop a more reasoned understanding of the moment of their career. This process proved to be revealing to the participants, realizing the events of their lives as experiences that trigger learning. The developed research also indicated the formative potential contained in the learning networks and in the contributions that formative proposals based on intergenerational dialogue can bring to teacher education and, in a special way, as a strategy to support the beginner teacher.